PHYSIOLOGICAL DISORDERS DUE TO THE USE OF PERSONAL PROTECTIVE EQUIPMENT ON NURSES IN THE ERA OF THE COVID-19 PANDEMIC: LITERATURE STUDY - Erika Nurwidiyanti; Teguh Santoso; Dwi Afrianti (Jurnal Keperawatan Respati Yogyakarta, 2022)
The use of personal protective equipment (PPE) is important for nurses when providing services to patients to avoid infectious diseases including COVID-19. However, continuous use of PPE can cause physiological problems such as headache, facial dermatitis, difficulty breathing, irritation, and discomfort. This study aims to determine various physiological disorders due to the use of PPE on nurses during the COVID-19 pandemic based on the results of a critical review of scientific articles. The search for scientific articles was carried out through the search engines Google Scholar, Pubmed, and EBSCO with the keywords personal protective equipment, physiological disorders, nurses, and the COVID-19 pandemic. The search is limited to 2020-2021, which is accessible in full text for free. The results of the literature study found 13 suitable articles. It is known that the use of PPE has effects such as headache, dermatitis, itching, rash, difficulty breathing, irritation, reactions to body skin tissue, acne and discomfort when used continuously for an indefinite period of time. It can be concluded that the use of PPE has a negative impact on the physiological condition of nurses if PPE is used continuously without regard to safety management in the use of PPE. Keywords: Nurses; The COVID-19 Pandemic; Personal Protective Equipment; Physiological Disorders